THE INFLUENCE OF TEACHER COLLABORATION ON THE TEACHING EFFECTIVENESS IN THE MALDIVES - Al-Amin Mydin; Mohamed Nasir (Journal of Islamic, Social, Economics and Development, 2023)
Teacher collaboration has emerged as a crucial factor influencing teaching effectiveness in education. This study aims to comprehensively level teacher collaboration and identify the influence of teacher collaboration on teaching effectiveness in the Maldives. Using a cross-sectional research design, data were collected from 390 teachers working in schools across the Maldives. The collected data were analysed using SPSS and structural equation modeling with smartPLS 3.3.7. This study contributes to the existing body of knowledge by providing a comprehensive examination of the multifaceted impact of teacher collaboration on various aspects of instructional delivery, including teacher-student interactions and student-learning regulation. The results show that the level of teacher collaboration is at a moderate low level. However, there is an influence between teacher collaboration on teaching effectiveness in the Maldives The findings offer valuable insights for educational practitioners, policymakers, and researchers who seek to enhance teaching effectiveness and improve the overall quality of education in the Maldives and beyond.